Necrolytic acral erythema in a Chinese patient with hepatitis C and hepatitis B virus coinfection - Ruzeng Xue; Amira Elbendary; Tieqiang Wu (Anais Brasileiros de Dermatologia, 2019)
Abstract: Necrolytic acral erythema is a distinct erythema that has been described as an extrahepatic manifestation of hepatitis C virus infection. Most reported cases have been in Africa, especially Egypt. We report the first case (to the best of our knowledge) of necrolytic acral erythema in a Chinese patient with HCV and HBV coinfection. We aim to increase awareness for recognizing this condition in the Chinese population.